Penerapan Program Tahfidz Al-Quran untuk Meningkatkan Kemampuan Literasi Siswa Madrasah Aliyah Ar-Rahman Ciamis - Iing Nurhidayat (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2023)
The research background is the condition of the Madrasah Gead, who must be able to design the direction of educational institutions on a civilized path so that the institution will continue to exist and be able to maintain the continuity of education to become a "long life education" with the implementation of the Al-Quran tahfidz program, which is expected to improve the literacy skills of MA Ar-Rahman students. The aim is to find out the planning, process, and success of implementing the Al-Quran tahfidz program to improve students' literacy skills. The benefits include increasing the performance of madrasa principals and teachers, implementing programs, and increasing students' literacy abilities. Research results in planning the implementation of the Al-Quran tahfidz program to improve students' literacy skills before implementing the tahfidz program obtained an average value of 80.48. After implementing the Al-Quran tahfidz program in cycle 1, an average value of 84.46 was obtained. Then, in Cycle II, an average value of 91.95 was obtained. In the process of implementing the Al-Quran tahfidz program in Cycle I, the ability of the teacher as program implementer The teacher's score was still below 75%, but in Cycle II, the score obtained by the teacher rose above 75%. Implementation of the program in cycle I was below 80%, but in cycle II it increased to above 80%.